Diagnostic accuracy of FNAC in diagnosis for causes of lymphadenopathy: a hospital based analysis - Singh, Arjun; Bhambani, Pawan; Nema, S. K. (International Journal of Research in Medical Sciences, 2017)
Introduction: The lymphadenopathy consist wide range of etiology from inflammatory process to a malignant condition and it is most common clinical presentation in outpatient department. Fine needle aspiration cytology is a simple, safe, reliable, rapid and inexpensive method of diagnosis in lymph nodes. Aims and objectives: To find out diagnostic accuracy of FNAC in lymphadenopathy and common pattern of lymphadenopathy in our institute. Methods: This prospective study was carried out in the department of Pathology of Index Medical College Hospital and research Centre, Indore, India from June 2011 to May 2013. The patients with palpable lymph nodes were included in this study. The slides were stained with Papanicolaou and May Grunewald Geimsa stain.Special stain like Ziel Neelson, Alcian blue was done whenever is required. A detailed analytic study was performed for correlation of Cyto-histopathological diagnosis. Results: The result shows male to female ratio of 1.0:0.8. The age of the patients ranges from 2 to 79 year with mean age of 32 years. The study shows reactive hyperplasia 149 (33.38%), tubercular lymphadenitis 177 (39.77%), granulomatous lymphadenitis 32(7.1%), lymphoma 25 (5.5%), metastatic carcinoma 40 (8.9%) and others 22 (4.9%). We found cyto-histpathological concordant in 161 (95.8%) cases and discordant in 7 (4.2%) cases. Conclusion: The sensitivity of FNAC in lymphoma and metastatic tumors is 81.48% and 97.5% with test accuracy of 96.5% and 99.4% respectively. Hence FNAC should be used as preliminary screening investigation in all forms of lymphadenopathy and interpretation should be done in conjunction with clinical picture of the patients.